Primary tumor delineation based on 18FDG PET for locally advanced head and neck cancer treated by chemo-radiotherapy. Issue 1 (July 2015) - Leclerc, Mathieu; Lartigau, Eric; Lacornerie, Thomas; Daisne, Jean-François; Kramar, Andrew; Grégoire, Vincent
Abstract Purpose/objective The use of FDG-PET for target volume delineation has been validated by our group for patients with locally advanced head and neck squamous cell carcinoma (HNSCC) treated by concomitant chemo-radiotherapy providing a strict methodology for image acquisition and segmentation. The aims of this study were (1) to confirm these results in a multicentric setting, and (2) to evaluate the clinical outcome in a prospective series of patients treated with FDG-PET scan-based radiotherapy planning. Material/methods Forty-one patients with stage III or IV HNSCC were included in this prospective multicentric study from 2007 to 2009. Before treatment, each patient underwent head and neck endoscopy, contrast enhanced CT or MRI and FDG PET scan. Patients were treated with invert or forward planning IMRT (using dose–volume constraints on PTVs and OARs). Primary tumor GTVPET were automatically delineated using a gradient based method and were registered on the planning CT. A prophylactic (50 Gy) and a therapeutic (70 Gy) primary tumor CTVPET were contoured using GTVPET volume along with data provided by endoscopy and pre-treatment imaging. Nodal CTV were delineated on the planning CT using internationally accepted guidelines. PTV was created by adding a security margin of 4–5 mm around CTVPET (PTVPET). At the end of the inclusion period after a minimal follow-up of 2 years, target volumes (GTVCT, CTVCT, PTVCT) for the primary tumors were re-delineated on the planning CT-scan using anatomic imaging only to perform a volumetric and a dosimetric comparison. Results Mean age of the population was 59 years. Oropharynx was the most common tumor location (68%), followed by oral cavity (17%), larynx (7%) and hypopharynx (7%). GTVPET contours were significantly smaller than GTVCT contours in all cases but one (average volume 28.8 ml vs 40.4 ml, p < 0.0001). The prophylactic primary tumor target volumes (CTV 50 Gy and PTV 50 Gy) based on PET scan were significantly smaller (p < 0.0001) in oropharynx cases. The boost target volumes (CTV 70 Gy and PTV 70 Gy) contoured on PET scan were also significantly smaller than the ones contoured on CT scan in all cases (p < 0.0001). The dosimetry comparison showed a significant decrease in parotid and oral cavity mean dose from the PET-based plans. After completion of chemo-radiotherapy, 5 patients had selective node dissection for suspicious lymph nodes on MRI and/or PET scan; only one had a positive pathological node. At a median follow-up of 3 years, the relapse-free and overall survival rates were respectively 32% and 43%. No marginal recurrence (in the CTVCT but outside the CTVPET) was observed. Conclusion This study confirms that the use of 18FDG-PET translated into smaller GTV, CTV and PTV for the primary tumor volumes in comparison with the use of CT. PET planning also demonstrated an improvement on dosimetry by lowering dose to certain organs at risk.